Prevention and treatment of wound complications at alloplasty of the complex abdominal wall defects - R. B. Lysenko (Zaporožskij Medicinskij Žurnal)
One of the major reasons causing the unsatisfactory results of the alloplasty of complex abdominal wall defects (CAWD) is the development of wound complications (WC), the frequency of which varies from 7.9 to 49.2%.